PENYULUHAN PENGOLAHAN LIMBAH TERNAK MENJADI PUPUK KANDANG (ORGANIK) DAN PEMBUATAN PESTISIDA ORGANIK - Agus Taufiq (Asian Journal of Innovation and Entrepreneurship, 2015)
Dusun Klumprit II is a dusun that located in Wukirharjo, Prambanan, District Sleman, Province of Yogyakarta. Dusun Klumprit II is a prosperous dusun with themajority of livelihoods are in agricultural and livestock. In this dusun there are alsoseveral home industries such as timber home industry. The residents of Dusun Klumprit II are dominated by old adult populations. The majority of the residents of DusunKlumprit II have a livestock, but unfortunately there were no further management forthe livestock waste. Mostly the house of the residents in Dusun Klumprit II also equipped with sanitary room (bathroom) with a waste bin. However, for the treatmentof kitchen waste (liquid and solid or organic waste) has not done well. The lack of publicunderstanding about the management the waste make the residents only handle it in simply way.Because of the lack of public understanding about the management of waste, it is needed to hold the livestock waste treatment counseling program into manure (organic)and organic pesticides of kitchen waste. The benefit from this program is there are knowledge about the products that can be made from the waste of kitchen and livestockbecame fertilizers and organic pesticides that also can be used directly by the residents that have agricultural land. The results that achieved by this program are the residents’insight and understanding became better.